The Development of Forest Policy in India-The forgotten Policy: Sir Herbert Howard's Post-War Policy of 1944 - Taylor II, George F. (Indian Forester, 1982)
Formulated by inspector-General Howard as part of a comprehensive re-examination of Government policy in the post-war years, the Post-War Forest Policy of 1944 was quickly engulfed in the events that led to independence in 1947. Although never adopted as official polley, this 'forgotten' document provides a valuable indication of policy direction at the end of the colonial period. The historical context of this reformulation is examined and changes in poliey direction are assessed. Attention is also directed to the deliberations of the Soil Conservation and Afforestation Sub-Committee of the National Planning Committee and to the parallel development of forest policy direction during the period under review.